An In Vitro Model for Identifying Cardiac Side Effects of Anesthetics. (January 2020) - Chang, Alex C. Y.; Chang, Andrew C. H.; Nicin, Luka; Weber, Gerhard J.; Holbrook, Colin; Davies, M. Frances; Blau, Helen M.; Bertaccini, Edward J.
Abstract : The understanding of anesthetic side effects on the heart has been hindered by the lack of sophisticated clinical models. Using micropatterned human-induced pluripotent stem cell–derived cardiomyocytes, we obtained cardiac muscle depressant profiles for propofol, etomidate, and our newly identified anesthetic compound KSEB01-S2. Propofol was the strongest depressant among the 3 compounds tested, exhibiting the largest decrease in contraction velocity, depression rate, and beating frequency. Interestingly, KSEB01-S2 behaved similarly to etomidate, suggesting a better cardiac safety profile. Our results provide a proof-of-concept for using human-induced pluripotent stem cell–derived cardiomyocytes as an in vitro platform for future drug design.